Risk classification and barrier of implementing risk management in oil and gas construction companies - Dehdasht, Gholamreza (Penerbit UTM Press, 2015)
Risk management is one of the most essential and significant part of construction projects due to assuring the attainment of project goals. Because of increasing global energy, more attention is needed to be paid towards risk management in oil and gas companies. The aim of this study is to improve the implementation of risk management within contractor companies in the oil and gas construction project through the evaluation of the most import risk groups and the barriers of implementing risk management in this part of industry. The current study is carried out in Iran and the scope of study includes only the construction project in oil and gas companies. A total of 48 questionnaires were distributed to the respondents and only 35 were obtained duly answered. The data was analyzed using SPSS software during the preliminary stage of this study, a variety of risk groups have been studied, six of it were identified to be the most probable in oil and gas construction projects which includes financial, technical, contractual, design and construction, policy and political, and weather and environmental risk groups. Among these groups “financial risk” is the most critical group, while “weather and environmental” is the least critical group. The important barriers of implementing risk management are lack of expertise in techniques, lack of familiarity with techniques and lack of information and knowledge.